Studi Sedimentasi Pada Saluran Intake PLTU Barru - Chairul Paotonan; Arsil (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2022)
Increasing the cooling capacity of generator engines or condenser engines by utilizing sea water at PLTU Barru requires dredging the intake channel with a dredging length of ±80 m and a depth of -4m LWS. The problem is that dredging the intake canal has the potential to cause silting back in the area that has been dredged due to coastal hydrodynamic processes which can cause blockage of the intake canal and disrupt the process of the pumping system and the generating system as a whole. A study is needed to assess the potential for sedimentation around the dredging area. This research uses primary data and secondary data. The primary data consists of bathymetry data, currents, tides and bottom sediments and water samples. While the secondary data includes comparative wave and tidal data as well as the design of the dredging plan. Wave data is sourced from the European Center for Medium-Range Weather Forecasts (ECMWF) while comparative tide data is obtained from the Geospatial Information Agency (BIG). The data obtained is then analyzed to obtain the parameters of currents, tides, sediment and breaking waves as well as sediment transport along the coast. Calculation of sediment flows and transport was also carried out by numerical modelling using a surface-water modelling system (SMS). Furthermore, by using the results of analytical sediment transport analysis and numerical modelling, the thickness of the trapped sediment is calculated in the intake canal after dredging. The results of numerical modelling analysis show that the potential for sedimentation at the study site originates from currents due to tides and currents due to breaking waves. The predicted potential for sedimentation due to tidal currents and broken wave currents for 1 year is 43.64 m3 and 1,589.93 m3 respectively with a sediment thickness of 1.2 meters from the bottom of the excavation so that intake channel maintenance is required at least once a year.